2020
DOI: 10.1002/jmv.26356
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of oral HPV infection among a healthy Iranian population; Kurdistan, West of Iran

Abstract: Human papillomavirus (HPV) infection has implicated in the development of some of the oral/oropharyngeal cancers. However, controversy still exists regarding the prevalence of oral HPV (OHPV) and its risk factors. This study aimed to determine the prevalence and variables of OHPV infection in a healthy Iranian population. This study evaluated 300 oral rinse samples. Following the oral and dental examination of participants and filling out a self‐administered questionnaire; samples collected by swishing and gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
(94 reference statements)
3
5
0
Order By: Relevance
“…In the 20–39 and 40–59 age groups, the presence of oral HPV may be caused by sexual activity. Similar to our data, studies in other countries have found that the age group around or over the age of 60 has the highest HPV presence in the oral cavity [ 6 , 19 , 20 ]. For adults over the age of 60, the number of positive oral HPV cases may be associated not only with sexual habits, but also with decreased immunity.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the 20–39 and 40–59 age groups, the presence of oral HPV may be caused by sexual activity. Similar to our data, studies in other countries have found that the age group around or over the age of 60 has the highest HPV presence in the oral cavity [ 6 , 19 , 20 ]. For adults over the age of 60, the number of positive oral HPV cases may be associated not only with sexual habits, but also with decreased immunity.…”
Section: Discussionsupporting
confidence: 92%
“…Oral HPV infections are the result of sexual behavior; however, recent evidence suggests a possible mouth-to-mouth transmission through saliva [ 3 ]. The presence of HPV genotypes in the oral cavity in various studies has been estimated up to 20% [ 6 , 13 , 14 , 15 , 16 , 17 , 18 ]. In our study, the incidence of HPV was low and amounted to 11.5% (53/461).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the use of vitamin C and carotenoids can be used to decrease the HPV infection persistence. 14,30 In the oral cavity, smoking affects the immunological functions, including innate and adaptive immune responses. 5 The acquisition and persistence of HPV infection increases in the individuals who use tobacco, as it might inhibit the immune function and causes direct damage to the cells.…”
Section: Resultsmentioning
confidence: 99%